Global solutions to the free boundary value problem of a chemotaxis-Navier–Stokes system. (1st May 2023) - Hou, Qianqian
Abstract: In this paper, we investigate the global solvability of the chemotaxis-Navier–Stokes system on a three-dimensional moving domain of finite depth, bounded below by a rigid flat bottom and bounded above by the free surface. Completing the system with physical boundary conditions on the free surface that match the boundary descriptions in the experiments and numerical simulations, we establish the global existence and uniqueness of solutions near a constant state ( 0, c ˆ, 0 ), where c ˆ is the saturation value of the oxygen on the free surface. To the best of our knowledge, this is the first analytical work for the well-posedness of chemotaxis-Navier–Stokes system on a time-dependent domain.